If your question is (sqrt x-2)= 1, then (sqrt x-2)^2 = 1^2 [meaning, square both sides to get rid of the square root]. You’ll get x - 2 = 1; add 2 to both sides, and you get x = 3.
If your question is (sqrt x) - 2 = 1 [meaning, the -2 is not included in the radical sighn], then add 2 to both sides, and you get (sqrt x) = 3. Square both sides, and you get x = 9.
2007-01-14 10:59:19
·
answer #1
·
answered by ♡♥ sHaNu ♥♡ 4
·
0⤊
0⤋
Let's see now...
sqrt x-2=1, therefore sqrt x=3 by adding 2 to both sides,
therefore x=9, by squaring both sides.
easy, huh?
2007-01-14 18:46:42
·
answer #2
·
answered by Rick H 1
·
0⤊
0⤋
sqrt x - 2 = 1
sqrt x - 2 = sqrt 1
x - 2 = 1
x = 2 + 1
x = 3 or sqrt x = 9
2007-01-14 18:51:14
·
answer #3
·
answered by wind_liao 2
·
0⤊
0⤋
1) sqrtx - 2=1
sqrtx = 3
x=9.
2) sqrt(x-2) = 1
x-2 = 1
x= 3.
2007-01-14 19:19:56
·
answer #4
·
answered by hirunisha 2
·
0⤊
0⤋
If sqrt(x)-2=1
sqrt(x)=3
x=9
If sqrt(x-2)=1
x-2=1
x=3
not sure which it was because of parenthesis
2007-01-14 18:47:24
·
answer #5
·
answered by Mr. Chemistry 2
·
0⤊
0⤋
sqrt(x - 2) = 1
square both sides
x - 2 = 1
x = 3
ANS : x = 3
2007-01-14 20:39:02
·
answer #6
·
answered by Sherman81 6
·
0⤊
0⤋
squarroot of x-2=1 .. square both sides so x=3.
2007-01-14 18:49:24
·
answer #7
·
answered by gina_d 3
·
0⤊
0⤋
â(x-2)=1 square both sides
x-2=1 add 2 to each side
x=3
2007-01-14 18:57:44
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋